Implementation of The Merdeka Curriculum in The High School Chemistry Learning Process: Analysis of Variations in Hydrocarbon Material - Fajar Naqsyahbandi; Nova Irawati Simatupang; Fapriyan Wijoyo Mulyopratikno; Retno Arianingrum; Sri Atun (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2024)
This study aims to analyze the characteristics of hydrocarbon chemicals in the Merdeka curriculum and curriculum 13, as well as explore variations of hydrocarbon materials taught by teachers in various schools under the Merdeka Curriculum. The type of research used is descriptive qualitative through survey methods. Respondents in this study involved 24 chemistry teachers who worked in DKI Jakarta and Yogyakarta. The selection of respondents was random. The results of this study show that there are differences in the characteristics of hydrocarbon materials taught in the 2013 curriculum and the Merdeka curriculum. In the Merdeka curriculum, most chemistry teachers still do not differ much from each other even though they have been given freedom in teaching, with only slight variations in the selection of the material. Teachers consider materials in hydrocarbon topics very important and must be taught thoroughly because they will be useful in learning the next topic. In making decisions to teach hydrocarbon material, teachers should increase their understanding of learning objectives, student heterogeneity, limited reference sources, school facilities, and students' initial knowledge.